Calorimetric investigation of radiation-thermal synthesized lithium pentaferrite; Journal of Thermal Analysis and Calorimetry; Vol. 101, iss. 1 - Surzhikov A. P. Anatoly Petrovich; Pritulov А. M.; Lysenko E. N. Elena Nikolaevna; Sokolovskiy A. N.; Vlasov V. A.; Vasendina E. A. Elena Aleksandrovna (2010, 2010)
Title screen